1340A Trial of Modern Sample Frames and Modes: The WA Health and Wellbeing Surveillance System. (2nd September 2021) - Patterson, Candice; Dombrovskaya, Mikhalina; Landrigan, Tim
Abstract: Background: The Health and Wellbeing Surveillance System (HWSS) monitors the health status of the WA population. Its reliance on a landline sample frame and Computer Assisted Telephone Interview (CATI) must shift to mobile phone sample frames and novel online completion options, improving the representativeness of the HWSS data to the WA population. Methods: Concurrent surveys in 2020 were run using three sample frames, the 2013 Electronic White Pages (EWP), the WA Electoral Roll (WAER) and a Sensis consumer database. The survey modes explored included CATI, online, and dual mode. Responses were weighted to the WA population. Response rates were compared between frames and modes. Differences in demographics, health risk factors, conditions and behaviours were investigated by comparing prevalence estimates and logistic regression modelling. Results: Response rates were 20% for EWP CATI, 41% for Sensis CATI, 16% for Sensis online, and 10% for WAER online. Compared to EWP, the WAER and Sensis frame respondents were younger, had higher incomes and better education. Online respondents had higher prevalence of high psychological distress and lower prevalence of smoking compared with CATI. Conclusions: The WAER and Sensis consumer database are valid sample frame options for the future of the HWSS. CATI gave the highest response rates, yet respondent differences by frame and mode were evident. WA Health is further exploring these options of modern sample frames and survey modes in 2021. Key messages: Population health surveillance systems must modernise their sample frames and data collection modes to continue to provide reliable health prevalence estimates.